Increased Frequency of Peripheral B and T Cells Expressing Granulocyte Monocyte Colony-Stimulating Factor in Rheumatoid Arthritis Patients - Makris, Anastasia; Adamidi, Sofia; Koutsianas, Christos; Tsalapaki, Christina; Hadziyannis, Emilia; Vassilopoulos, Dimitrios (Frontiers in Immunology, 2018)
Objectives: Granulocyte monocyte colony stimulating factor (GM-CSF) is currently considered a crucial inflammatory mediator and a novel therapeutic target in rheumatoid arthritis (RA) despite the fact that its precise cellular sources remain uncertain. We studied the expression of GM-CSF in peripheral lymphocytes from RA patients and its change with anti-rheumatic therapies. Methods: Intracellular GM-CSF expression was assessed by flow cytometry in stimulated peripheral B (CD19+) and T (CD3+) cells from RA patients (n=40), disease (n=31: osteoarthritis n=15, psoriatic arthritis n=10, systemic rheumatic diseases n=6) and healthy (n=16) controls. The phenotype of GM-CSF+ B cells was assessed as well as longitudinal changes in GM-CSF+ lymphocytes during methotrexate (MTX, n=10) or anti-tumor necrosis factor (TNF, n=10) therapy. Results: Among untreated RA patients with active disease (Disease Activity Score 28-CRP=5.6 ± 0.89) an expanded population of peripheral GM-CSF+ B (4.1 ± 2.2%) and T (3.4 ± 1.6%) cells was detected compared both to disease (1.7 ± 0.9%, p<0.0001 and 1.7 ± 1.3%, p<0.0001, respectively) and healthy (0.3 ± 0.2 %, p<0.0001 and 0.6 ± 0.6%, p<0.0001) controls. RA GM-CSF+ B cells displayed more commonly a plasmablast or transitional phenotype (37.12 ± 18.34% vs. 14.26 ± 9.46 %, p=0.001 and 30.49 ± 15.04 % vs. 2.45 ± 1.84 %, p<0.0001, respectively) and less a memory phenotype (21.46 ± 20.71% vs. 66.99 ± 16.63 %, p<0.0001) compared to GM-CSF- cells. GM-CSF expression in RA patients did not correlate to disease duration, activity or serological status. Anti-TNF treatment led to a statistically significant decrease in GM-CSF+ B and T cells while MTX had no significant effect. Discussion: This is the first study showing an expanded population of GM-CSF+ B and T lymphocytes in patients with active RA which declined after anti-TNF therapy.